(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the study was to assess the possibility of using willow for remediation of landfills and dumps of mining and post-mining excavations. The first section presents the characteristics of degraded areas, basic definitions and legal acts concerning the process of restoration and repair inside this natural change. In the second part of the study focuses on the properties of the willow to accumulate heavy metals and elements of chemically conta-minated sites. It was found that willow can be used in the process ofphytoextraction and phyto stabilization. Fitoekstrakcyjny measurable effect on a willow can be obtained in the case of cadmium and zinc.